2020
DOI: 10.1177/0954411920967146
|View full text |Cite
|
Sign up to set email alerts
|

Design of dental implant using design of experiment and topology optimization: A finite element analysis study

Abstract: Ever since the introduction of topology optimization into the industrial and manufacturing fields, it has been a top priority to maximize the performance of any system by optimizing its geometrical parameters to save material while keeping its functionality unaltered. The purpose of this study is to design a dental implant macro-geometry by removing expendable material using topology optimization and to evaluate its biomechanical function. Three-dimensional finite element models were created of an implant embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
2
19
0
2
Order By: Relevance
“…43 Previous FEA studies reported lower forces on the implant, abutment, and screws than those reported in the present study. 20,21,25,26 The reason for this may be the difference in the implant models investigated in the studies, whether the models are more complex, the difference in the number of nodes and elements, the loadings made under different conditions, and the use of different analysis methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…43 Previous FEA studies reported lower forces on the implant, abutment, and screws than those reported in the present study. 20,21,25,26 The reason for this may be the difference in the implant models investigated in the studies, whether the models are more complex, the difference in the number of nodes and elements, the loadings made under different conditions, and the use of different analysis methods.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, no previous studies have compared aggressively threaded implants in terms of the stress on different bone types, except for finite element studies of a few thread designs. 17,19,20,22,[24][25][26] The null hypothesis of this study was that there is no difference in the stress levels of different thread designs of implants with different bone types and different abutment angles.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…It is concluded that DOE can play a major role in the design of implants. 25 Taguchi method is one of the most common methods for designing the factorial test. 26 The L 25 orthogonal array was used for the levels shown in Table 4.…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%